2017
DOI: 10.1152/ajplung.00084.2017
|View full text |Cite|
|
Sign up to set email alerts
|

An ex vivo model to induce early fibrosis-like changes in human precision-cut lung slices

Abstract: Idiopathic pulmonary fibrosis (IPF) is a devastating chronic interstitial lung disease (ILD) characterized by lung tissue scarring and high morbidity. Lung epithelial injury, myofibroblast activation, and deranged repair are believed to be key processes involved in disease onset and progression, but the exact molecular mechanisms behind IPF remain unclear. Several drugs have been shown to slow disease progression, but treatments that halt or reverse IPF progression have not been identified. Ex vivo models of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
172
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 177 publications
(193 citation statements)
references
References 21 publications
4
172
0
Order By: Relevance
“…However, even this complex 3D multicell model of the lung can only partly reflect the properties of native lung tissue. For instance, it does not represent an intact epithelial‐endothelial tissue barrier, ALI conditions as encountered in the lung and an intact immune system causing nonphysiological responses . Moreover, these top‐down approaches still require the use of animals or donor organs, while bottom‐up approaches bear the potential of animal free drug/toxicity testing.…”
Section: Future Directions: Biomimetic Models Of the Lungmentioning
confidence: 99%
“…However, even this complex 3D multicell model of the lung can only partly reflect the properties of native lung tissue. For instance, it does not represent an intact epithelial‐endothelial tissue barrier, ALI conditions as encountered in the lung and an intact immune system causing nonphysiological responses . Moreover, these top‐down approaches still require the use of animals or donor organs, while bottom‐up approaches bear the potential of animal free drug/toxicity testing.…”
Section: Future Directions: Biomimetic Models Of the Lungmentioning
confidence: 99%
“…Non-invasive imaging techniques remain unable to fully characterise the nature of fibrosis in the lung [8] and particularly the heart [9], resulting in a reliance upon ex vivo studies [10,11]. This has motivated in silico investigations, seeking to explain both the creation of different fibrotic patternings [12] and in the case of cardiac fibrosis, its pro-arrhythmic consequences [13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…To further investigate the functional consequences of highly upregulated profibrotic response we sought to measure the deposition of fibrillar collagen (tissue phenotypic marker of fibrosis) 3 in ECM of hPCLS. Other studies 10,20 have made attempts to use hPCLS for studying fibrotic signalling, however, a functional readout that confirms excess extracellular matrix deposition has been lacking. Not only in this model system but in other systems as well, only indirect readouts such as ELISA 57 of procollagen peptides or hydroxyproline levels in serum have been used to infer on fibrosis, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…While it is important to measure regulation of various markers of a pro-fibrotic process to validate induction of pro-fibrotic signalling, to better assess the functional consequences it is necessary to confirm that this signalling translates into higher extracellular deposition of fibrillar collagen. Several recent studies 10,20,21 have shown induction of pro-fibrotic signalling in ex-vivo cultured hPCLS using TGFß1 stimulation 10 or a cocktail of pro-fibrotic factors 20 but a validation of consistent and specific ECM deposition (fibrillar collagen in particular) is still lacking. Next we investigated whether the observed upregulation was translating into deposition of fibrillar collagens in the extracellular matrix.…”
Section: Induction Of Pro-fibrotic Signalling Upon Tgfß1 Stimulation mentioning
confidence: 99%
See 1 more Smart Citation